Transformasi Dan Pengembangan Kultur Sekolah Di Sekolah Menengah Pertama - Lampola Sitorus P (Mathematics Education Study Program, 2025)
This research aims to see how the transformation and development of school culture in State Junior High School 2 Pangururan. This school is a school that has successfully transformed and developed its school culture. This transformation can be seen from the improvement of the quality of education through increased achievement both academic and non-academic. In this process, the principal has a strategic role in initiating changes and running the program that has been prepared. Exemplary, approach and leadership are important keys that influence teachers to be actively involved in making changes. This research uses a qualitative approach.